2017
DOI: 10.1007/s00011-017-1124-5
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of cytokines gene promoters in IL-1β-treated human intestinal epithelial cells

Abstract: Our results suggest a potential role of IL-1β as modulator of DNA methylation in activated differentiated Caco-2 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Therefore, differentiated Caco‐2 cell monolayers represent a well‐characterized intestinal barrier model in vitro and have widely been used in bioavailability studies . On the other hand, differentiated Caco‐2 monolayers submitted to pro‐inflammatory action of LPS or cytokines have been proposed as in in vitro model of intestinal inflammation, which is useful for evaluating potential local effects of food, food components, or per oral drugs …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, differentiated Caco‐2 cell monolayers represent a well‐characterized intestinal barrier model in vitro and have widely been used in bioavailability studies . On the other hand, differentiated Caco‐2 monolayers submitted to pro‐inflammatory action of LPS or cytokines have been proposed as in in vitro model of intestinal inflammation, which is useful for evaluating potential local effects of food, food components, or per oral drugs …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that proinflammatory actions of IL‐1β in differentiated Caco‐2 cells also involve epigenetic mechanisms. In particular, IL‐1β is able to change the methylation status acting as demethylating agent …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations